Genetic Improvement Programs Advisory Programs in Africa and Asia - Komugisha, Basiita Rose; Trinh, Trong (WorldFish, 2022)
WorldFish Genetics Workshop 2022 - Presentation on the Genetic Improvement Advisory Programs in Africa and Asia.